Panin Dai-ichi Life Retirement Insurance to Prevent the Sandwich Generation - Sihombing, Gresia Amelia; Berlianti; Siregar, Hairani; Muhammad Iffat Rozaan; Erga Dwo Winatra (Triwikrama: Jurnal Ilmu Sosial, 2024)
The phenomenon of the "sandwich generation" refers to individuals who are caught between caring for aging parents and supporting their own children. This situation creates financial and emotional stress, as they struggle to meet the needs of both generations simultaneously. In Indonesia, this issue is becoming more prevalent due to the aging population and rising living costs. One potential solution to mitigate this burden is the adoption of retirement insurance products, such as the Panin Dai-ichi Life Pension Guarantee Insurance. This study aims to examine how the implementation of such insurance can help the sandwich generation in Indonesia to prepare for their own future while reducing the financial strain caused by their familial responsibilities. The research explores the features and benefits of the Panin Dai-ichi Life Pension Guarantee Insurance, demonstrating how it can provide financial security for individuals in their retirement years, thereby alleviating some of the financial pressures faced by the sandwich generation. This paper concludes that insurance solutions like Panin Dai-ichi Life's Pension Guarantee can play a crucial role in addressing the financial challenges associated with the sandwich generation phenomenon